Potential of cultivation of medicinal plants in Jaffna to promote indigenous drug preparation with special reference to ashwagandha - Suvanthini, S.; Mikunthan, G.; Thurairatnam, S. (Journal of Siddha symposium,Department of Indigenous medicine, Northern Province, 2013)
Medicinal plants continue to be an important therapeutic aid for alleviating ailments of humankind. Increasing interest by multinational pharmaceutical companies and domestic manufacturers of herbal-based medicines is contributing significant economic growth of the global medicinal plants sector. Ashwagandha, Withania somnifera is highly reputed medicinal plant in Sri Lanka belongs to family Solanaceae. It is widely utilized in indigenous medical practice over 3000 years. Root is the economic important part but other parts also credited with medicinal properties. It possesses anti-inflammatory, antitumor, antistress, antioxidant, immunomodulatory, hemopoetic, and rejuvenating properties. Specifically, the literature was reviewed for articles pertaining to potentialities of ashwagandha cultivation and the challenges. Being a drought tolerant plant, it has the suitable climatic condition for the cultivation in dry zone. The need for shifting of cultivation of crops from only food to other crops especially medicinal crops, fibres etc is urged. These crops are essential to substitute some of the crops that require continuous spraying of pesticide to minimize the cost of production and to free from polluting environment. This is the apt time to look for alternate crops to be incorporated into the cultivation schedule to maximize the profit of the farmer. One such alternative is incorporation of medicinal crops into the system. Demand on medicinal plants is very high and especially the root part of aswagantha is one among them. Fibrous root, poor technical knowledge, inadequate awareness and pest and diseases are the major challenges for its cultivation. But the ease of cultivation and high price for the roots are attracting the farmers for large scale cultivation in Jaffna. In addition to the roots, leaves and seeds are also marketed enhancing the profits of the farmers. The future is excellent for extending its cultivation and production of numerous value added products from its roots.
Keywords: Withania somnifera; medicinal plant; Root